ANALISIS KANDUNGAN LOGAM BERAT MERKURI (Hg), TIMBAL (Pb) DAN KADMIUM (Cd) PADA IKAN BAUNG (Hemiarius stornii) YANG DIPEROLEH DARI SUNGAI KAHAYAN KALIMANTAN TENGAH - aqnes budiarti; rini yeni susanti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2008)
ABSTRACTGold mining waste and other human being’s rubbish containing heavy metal thrown into the water would be contaminating river. This condition will push to the bio-magnification and bio-accumulation under water living. The measured variables were Mercury (Hg), Lead (Pb) and Cadmium (Cd) content which were concentrated in Baung fish body. The researched environment parameters were Mercury (Hg), Lead (Pb) and Cadmium (Cd) containing in the water and the rate of DO, BOD and COD. Block model was used in this experimental model of this research. Sampling technique used was simple random sampling, with Baung fish and the water from Kahayan river as samples. Hg, Pb and Cd were measured with Atomic Absorption Spectrophotometer. The result of this research indicates that the metal content in Baung fish in point I, that is 150 meters before the gold mining site : Hg 0.09 mg/kg, Pb 0.16 mg/kg, Cd 0.01 mg/kg, then point II that is 0 meter of the gold mining site : Hg 0.09 mg/kg, Pb 0.20 mg/kg, Cd 0.01 mg/kg and in point III that is 150 meters after the gold mining site : Hg 0.08 mg/kg, Pb 0.19 mg/kg, Cd 0.01 mg/kg. Metal content of Kahayan river water in point I : Hg 0.007 mg/L, Pb 0.030 mg/L, Cd 0.005 mg/L, then point II Hg 0.007 mg/L, Pb 0.030 mg/L, Cd 0.005 mg/L and in point III : Hg 0.006 mg/L, Pb 0.030 mg/L, Cd 0.005 mg/L. BAF in point I : Hg 2.4518, Pb 1.1478, Cd 0.4067, point II : 2.7667, Pb 1.3689, Cd 0.4200, and in point III : Hg 2.8703, Pb 1.3178, Cd 0.4200. Hg, Pb and Cd in Baung fish is still under the limit of permittable metal contamination in fish and its differential products according to the government regulation from Dirjen POM No. 03725/B/SK/VII/89. The rate of DO, BOD and COD from this three locations have over the permanent quality of PP No.82 in 2001 about water quality management and water pollution management. Keywords : Heavy metal Mercury (Hg), Lead (Pb) and Cadmium (Cd), Atomic Absorption Spectrophotometer, Baung fish (hemiarius stornii).